Risk Factor Burden, Heart Failure, and Survival in Women of Different Ethnic Groups: Insights From the Women's Health Initiative. (May 2018) - Breathett, Khadijah; Leng, Iris; Foraker, Randi E.; Abraham, William T.; Coker, Laura; Whitfield, Keith E.; Shumaker, Sally; Manson, JoAnn E.; Eaton, Charles B.; Howard, Barbara V.; Ijioma, Nkechinyere; Cené, Crystal W.; et al.
Abstract : Background: The higher risk of heart failure (HF) in African-American and Hispanic women compared with white women is related to the higher burden of risk factors (RFs) in minorities. However, it is unclear if there are differences in the association between the number of RFs for HF and the risk of development of HF and death within racial/ethnic groups. Methods and Results: In the WHI (Women's Health Initiative; 1993–2010), African-American (n=11 996), white (n=18 479), and Hispanic (n=5096) women with 1, 2, or 3+ baseline RFs were compared with women with 0 RF within their respective racial/ethnic groups to assess risk of developing HF or all-cause mortality before and after HF, using survival analyses. After adjusting for age, socioeconomic status, and hormone therapy, the subdistribution hazard ratio (95% confidence interval) of developing HF increased as number of RFs increased ( P <0.0001, interaction of race/ethnicity and RF number P =0.18)—African-Americans 1 RF: 1.80 (1.01–3.20), 2 RFs: 3.19 (1.84–5.54), 3+ RFs: 7.31 (4.26–12.56); Whites 1 RF: 1.27 (1.04–1.54), 2 RFs: 1.95 (1.60–2.36), 3+ RFs: 4.07 (3.36–4.93); Hispanics 1 RF: 1.72 (0.68–4.34), 2 RFs: 3.87 (1.60–9.37), 3+ RFs: 8.80 (3.62–21.42). Risk of death before developing HF increased with subsequent RFs ( P <0.0001) but differed by racial/ethnic group (interaction P =0.001). The number of RFs was not associated with the risk of death after developing HF in any group ( P =0.25; interaction P =0.48). Conclusions: Among diverse racial/ethnic groups, an increase in the number of baseline RFs was associated with higher risk of HF and death before HF but was not associated with death after HF. Early RF prevention may reduce the burden of HF across multiple racial/ethnic groups. Abstract : Supplemental Digital Content is available in the text.